Structural response and sensitivity analysis of granular and asphaltic overlayment track considering linear viscoelastic behavior of asphalt - Setiawan Dian M. (De Gruyter, 2021)
This study investigated the structural response of granular and asphaltic overlayment of rail track considering the linear viscoelastic behavior of asphalt. The calculation of the tensile strains at the bottom of the asphalt layer, the compressive stresses at the top of the subgrade layer, and the service life of the granular and the asphaltic overlayment rail track were conducted using the KENTRACK software. Furthermore, the sensitivity analysis by changing different factors was studied in this paper. The results of this study indicate that the asphaltic overlayment rail track structure has a much longer predicted service life than the granular rail track. It was also shown that the sub-grade compressive stress is more sensitive to the change in subgrade modulus than the change in ballast-sub-ballast-asphalt layer thickness and the change in binder type, respectively. In addition, the asphalt tensile strain is more sensitive to the change in asphalt layer thickness than the change in subgrade modulus and the change in binder type, respectively. These findings also enhance our understanding that subgrade compressive stress and asphalt tensile strain in the asphaltic overlayment track are more sensitive to the change in asphalt layer thickness than the change in binder type.